FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016 - Ardila, Yurni (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2018)
This study aims to analyze and provide empirical evidence about the factors that influenceAuditor Switching on consumer goods companies listed on the IDX in 2010-2014. The selection ofsamples in this study used a purposive sampling method. The number of companies used in this studyconsisted of 24 companies during the period 2010-2014. The research method used is descriptivequantitative method, while the hypothesis testing method uses logistic regression. The results of thisstudy can be seen only the audit tenure shows a significance level (p) of 0,000, which means it issmaller than α = 5%. So it can be concluded that the audit tenure has an effect on the SwitchingAuditor. While the size of the Public Accountant Office, management change, and audit delay doesnot affect the turnover of the Public Accountant Office (Auditor Switching.) Testing together(simultaneous) shows a significance level (p) of 0,000 means smaller than α = 5%. So that it can beconcluded that the size of the Public Accounting Firm, management change, audit tenure, and auditdelay have an effect on the Switching Auditor.